1996
DOI: 10.1111/j.1151-2916.1996.tb08608.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Spinel Powders by Flame Spray Pyrolysis of a Magnesium Aluminum Double Alkoxide

Abstract: Ultrafine crystalline spinel powder has been prepared using flame spray pyrolysis of alcoholic solutions of a novel double alkoxide precursor. The particles produced are spherical, dense, single crystals with diameters of 10–100 nm and specific surface areas ranging from 40 to 60 m2/g. Powder production rates of 50–100 g/h are achieved using a bench‐top apparatus. Particle formation appears to occur by rapid oxidation of the organic ligands followed by nucleation and growth from oxide species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(103 citation statements)
references
References 20 publications
0
97
0
1
Order By: Relevance
“…However, delivery of a liquid precursor into the flame may be the most effective route, since a broad range of less volatile raw materials is available that can be dissolved in organic solvents or even water, allowing relatively simple liquid precursor handling and dosing. In particular, flame spray pyrolysis (Bickmore et al, 1996;Mädler et al, 2002) that benefits from self-sustaining high temperature flames has been shown to be a versatile and scalable method for the production of single-and multi-component oxide and even metal nanoparticles, as is apparent from recent reviews (Teoh et al, 2010;Athanassiou et al, 2010;Strobel and Pratsinis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, delivery of a liquid precursor into the flame may be the most effective route, since a broad range of less volatile raw materials is available that can be dissolved in organic solvents or even water, allowing relatively simple liquid precursor handling and dosing. In particular, flame spray pyrolysis (Bickmore et al, 1996;Mädler et al, 2002) that benefits from self-sustaining high temperature flames has been shown to be a versatile and scalable method for the production of single-and multi-component oxide and even metal nanoparticles, as is apparent from recent reviews (Teoh et al, 2010;Athanassiou et al, 2010;Strobel and Pratsinis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Transparent ceramic garnets were formed at LLNL using stoichiometric mixed metal oxide particles synthesized via flame spray pyrolysis (FSP), a nanoparticle production method developed by Pratsinis and co-workers [13] and Laine and co-workers [14]. Synthesis of FSP nanoparticles was carried out at LLNL, as well as by Nanocerox, Inc.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…As business interests focus on high-value products, small companies such as Nanogram in Milpitas, California; nGimat in Atlanta, Georgia; Tal in Michigan; and Turbobeads, HeiQ, and Nanograde in Zurich, Switzerland, to name only a few, use flame aerosol technology to make such products. To that effect, combustion of sprays of organic solutions similar to the furnace process for carbon black (Kühner & Voll, 1993) but for ceramics (Sokolowski et al, 1977;Lewis, 1991;Bickmore et al, 1996;Mädler et al, 2002a) and flame pyrolysis of sprays of aqueous solutions of inorganic precursors (Marshall et al, 1971;Purwanto et al, 2008) relieve the constraint of using vaporizable precursors and create unprecedented opportunities for synthesizing sophisticated materials beyond the simple oxides of the recent past (Strobel & Pratsinis, 2007). Most notably, Johnson Matthey, a leading manufacturer of heterogeneous catalysts, actively explores such aerosol technology for synthesizing a wide spectrum of nanomaterials (Figure 4).…”
Section: Zno Ni Wc and Other Materialsmentioning
confidence: 99%